An honorable deception - White, Roseanna M. (White, Roseanna M. Imposters, 2024)
"Lord Yates Fairfax, leader of the secretive Imposters, is pulled into a mysterious case by the beautiful Lady Alethia. Joined by one of his oldest friends, Lady Lavinia, their investigations reveal society's darkest secrets, forcing them to confront the unsettling reality that the gentry isn't always noble, and truth isn't always honorable"--